Research Synthesis on Differential Factors Associated with Health Behaviors Between Young-Old and Old-Old Adults in Thailand: A Meta-Analytical Approach - Srithong, Theera; Bawornkulwat, Nivet; Lamprom, Wanjai (Social Science Innovation and Applied Management (SIAM), 2025)
This study synthesized factors associated with health behaviors among Thai elderly through systematic review of ten research articles published between 2015-2024. Findings revealed three main factor categories: personal factors (age, education, income, marital status), knowledge-attitude factors, and access-participation factors (elderly clubs, health check-ups, social support). Statistical analysis identified perceived benefits (r = 0.664, p<0.001) and social support (r = 0.537, p<0.001) as having the strongest positive correlations with health behaviors, while age showed a negative correlation (r = -0.227, p<0.01). Significant differences emerged between young-old (60-70 years) and old-old (71+ years) adults: young-old were primarily influenced by mental well-being (β = 0.42) and physical well-being (β = 0.38), whereas old-old were more affected by material support (β = 0.45) and intellectual well-being (β = 0.40). These differential patterns reflect evolving needs across the aging spectrum, requiring tailored intervention approaches. Despite high knowledge levels (48.89%) and positive attitudes (53.61%) among elderly, only 15.20% demonstrated high-level health behaviors, highlighting a substantial knowledge-practice gap. Regional variations were also observed, with stronger social support correlations in rural northeastern communities (r = 0.61) compared to urban central areas (r = 0.42). These findings suggest that health promotion strategies should be age-tailored and geographically contextualized, emphasizing psychological and physical dimensions for young-old adults while focusing on support systems and cognitive maintenance for old-old adults. Such differentiated approaches could enhance elderly quality of life while potentially reducing healthcare costs through more effective prevention and targeted interventions.